A Critical Review of Development Sociology: Theories and Policies - Bakhtiari, Samira (Journal of Entrepreneurship, Business and Economics; Vol 4 No 2 (2016), 2016)
Development sociology is an attractive field of research, as well as an interesting philosophical debate which a series of well known philosophers have concentrated upon, such as Marx, Durkheim, and Weber. Faced with an impasse, historians and other social scientists set out on a novel journey to examine different aspects of this concept. Thus, this paper tries to elaborate the concept, to review the history, to discuss the main topics in mainstream research, and finally to make policy recommendations based on the discussions. Research paper Reference to this paper should be made as follows: Bakhtiari, S. (2016). A Critical Review of Development Sociology: Theories and Policies, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 2, pp. 150–162.